Insight into metal-free carbon catalysis in enhanced permanganate oxidation: Changeover from electron donor to electron mediator - Peng Zhang; Peng Zhou; Jiali Peng; Yang Liu; Heng Zhang; Chuanshu He; Zhaokun Xiong; Liu, Wen; Bo Lai (Water Research, 2022)
Reports that the exploitation of metal-free carbon materials to enhance permanganate (PM) oxidation to abate organic pollution in water have emerged in recent publications. However, the activation mechanism and active sites involved are ambiguous because of the intricate physicochemical properties of carbon. In this study, reduced graphene oxide (rGO) as a typical carbon material exhibits excellent capability to boost permanganate oxidation for removing a wide array of organic contaminants. The simultaneous two reaction pathways in the rGO/PM system were justified: i) rGO donates to electrons to decompose PM and produce highly reactive intermediate Mn species for oxidizing organic contaminants; ii) rGO mediates electron transfer from organics to PM. Oxygen-containing groups (hydroxyl, carboxyl, and carbonyl) were justified as electron-donating groups, while structural defects (vacancy and edge defects) were shown to be critical for rGO-mediated electron transfer. Therefore, the oxidation pathway of the rGO/PM system can be controlled by regulating oxygen functional groups and structural defects. The changeover from electron donor to electron mediator by decorating surface active sites of carbon materials will be of great help to the design and application of carbocatalysts.
Keywords: Carbon catalysis; Electron transfer; Oxygen-containing groups; Permanganate; Structural defects